2017
DOI: 10.15561/20755279.2017.0301
|View full text |Cite
|
Sign up to set email alerts
|

Physical education of students, considering their physical fitness level

Abstract: Purpose:to determine effectiveness of students' physical education program, mainly directed at development of leading physical qualities. Material:100 students participated in experiment. In control group (n=50) all physical qualities were trained equally. In experimental group (n=50) loads were directed at training of leading (better trained) physical qualities. Results:we detected higher physical culture-sport activity of students in conditions of the author's program's application. Higher health related eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This separation enabled some differences in findings between younger and older students to be found. While for older ages PE seems to be less effective in promoting students' CRF [14,22,[25][26][27][28][29][30][31][32][33][34][35][36], for younger ages almost all studies suggested that PE classes improved the students' CRF [13,[21][22][23][24]. From a physiologic standpoint, CRF naturally increases as children grow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This separation enabled some differences in findings between younger and older students to be found. While for older ages PE seems to be less effective in promoting students' CRF [14,22,[25][26][27][28][29][30][31][32][33][34][35][36], for younger ages almost all studies suggested that PE classes improved the students' CRF [13,[21][22][23][24]. From a physiologic standpoint, CRF naturally increases as children grow-up.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, findings from older students (n = 26), with a wider age range (approximately 11 to 19 years), were mixed. A total of 15 findings from 14 studies showed that PE had a neutral effect on students' CRF (n = 15) [14,22,[25][26][27][28][29][30][31][32][33][34][35][36]. While, 11 findings from nine studies reported that PE had a positive effect in children's and adolescents' CRF [26][27][28][36][37][38][39][40][41].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This will ensure a rapid growth in the level of development of the basic physical qualities and motor abilities of the students. The scientists have found that there is a significant increase in the level of development of the leading physical qualities and physical health of the students engaged in physical exercises according to the individual programs taking into account the differences in the physical training of young people and their personal responses to various physical activities (Andres, 2017). Besides, the similar statements of the authors agree with the latest scientific research.…”
Section: Discussionmentioning
confidence: 55%
“…According to the authors, it is necessary to conduct the PE practical classes for the students with disabilities taking into account the individual characteristics of their diseases and the initial level of the physical development. Specialists have revealed that there is a significant increase in the level of development of the leading physical qualities and physical health of the students engaged in physical exercises with the help of the individual programs taking into account the differences in the physical training of the young people and their personal responses to different physical activities (Andres, 2017). Fortunately, the importance of a systematic PA for improving the level of motor development and the psychosocial status of the persons with disabilities and the difficulties of physical and mental development is emphasized by the specialists (Perić, Salapura, Džinović-Kojić, et al, 2018).…”
mentioning
confidence: 99%